News Processing for Intellectual Terrorism Phenomena in News Websites, Analytical Study: Kurdistan 24 and NRT Websites - Mohammed, Arsalan Rahman; Qadir, Sara Muhsin (Journal of University of Raparin, 2022)
The phenomenon of intellectual terrorism has emerged in different places and times within the framework of the media message. This phenomenon is closely related to the editorial policy of media channels, given the different editorial policy, work environment, and geopolitics in the Kurdistan Region, this study identified the cities of Erbil and Sulaymaniyah as research communities. The (Kurdistan 24) channel website in Erbil and the website of (NRT) channel in Sulaymaniyah were chosen as two research samples. The main problem of this study is about the extent to which the concept of intellectual terrorism is embodied in Kurdish news websites. It is also one of the manifestations of external influences that play a role in formulating the media message and editorial policy of the channel, because the embodiment of intellectual terrorism is more dangerous than terrorism in its general sense, especially since the main goal of intellectual terrorism is to terrorize the other party morally, and to prepare the ground for physical cleansing, distorting the mental image, and thus creating a new mental image.The main objective of this study is to analyze the content of the media message, in which the research samples direct the news to their receivers, and to reveal the hidden side of the media message. The study also deals with the extent to which the work environment and the political conflicts between the parties affect the formulation of the media message and the embodiment of intellectual terrorism in it. Besides defining and analyzing these concepts, phrases, and language, which in turn make up this message. This study, which is based on the content analysis method, shows the extent of the use and embodiment of intellectual terrorism through editorial language and policy by analyzing the news content of both samples. After evaluating the study questions by the evaluation experts, the researcher created tables for the shape and news content of the two samples. Within the content of the study, the concepts of terrorism and intellectual terrorism and their objective were explained from a scientific point of view, and then stations were reviewed on the history of intellectual terrorism in the Kurdistan Region, and the impact of political, economic and geographical conflicts on its appearance. Within the practical side of this study, and through (14) tables, vigorous efforts were made, in terms of form and content, to achieve and analyze these tables regarding the practice of intellectual terrorism in the news, on both (K24) and (NRT) websites. In conclusion, several of the most prominent results of the study were presented as follows:The news treatment of intellectual terrorism on the two websites that are directly related to the media work environment, their sources of funding, and their level of bias in presenting the contents and publishing news. The two websites also created a suitable environment for the emergence and nurturing of ideological terrorism, especially when the level of conflict is at its most intense.